Dragonfly Dominance (Order: Odonata) in the Danau Tangkas Natural Tourism Area, Tanjung Lanjut Village, Muaro Jambi Regency - Artika, Ulin; Kartika, Winda Dwi; Subagyo, Agus; Mursyd, Danial (Biospecies, 2024)
Dragonflies (Odonata) belong to the phylum Arthropoda class Insecta. Dragonflies are spread in various types of habitats, one of which is in the water area, namely Lake. Danau Tangkas is one of the natural tourism areas in Jambi province. Danau Tangkas is a conducive habitat for dragonfly breeding because the habitat conditions around Danau Tangkas are still beautiful with preserved vegetation. However, the Danau Tangkas area is a tourist area, so it has the potential to experience changes that can have an impact on the dragonfly dominance index. The study aims to analyze the dominance of dragonflies found in the Danau Tangkas natural tourism area. The type of research is exploratory descriptive research. Sampling was done using purposive sampling method. Sampling was carried out at 3 location points that have different characteristics. Made 3 stations with a length of 100 m each to the side and 100 m to the front so as to form a square line. Sample collection is done by hand collecting and using insect nets. Data analysis techniques using Simpson's dominance index calculation. The results of research that has been carried out in the Danau Tangkas  natural tourism area, obtained as many as 447 individuals, 9 species belonging to 3 families. So it is known that the dragonfly dominance index in the Tangkas Lake natural tourism area is low with a value of 0.4.